Three-Dimensional Osteosarcoma Models for Advancing Drug Discovery and Development - Monteiro, Cátia F. (2019)
Osteosarcoma (OS) is the most common primary malignant tumor of bonethat mainly affects children and adolescents. The currently available therapiesare not effective and the search for new OS anticancer drugs is extremelyurgent. Understanding the mechanisms that underlie the tumor progression,invasion, and metastasis is an essential step toward effective cancertherapies. Tissue engineering has given a great contribution to thedevelopment of reliable and cost-effective platforms for drug screening andvalidation through 3D in vitro models that more faithfully mimic the in vivopathophysiology than conventional 2D models. The progress in the field offunctional and biomimetic biomaterials in the development of 3D tissuemodels has provided tools for a close recapitulation of the highly complex anddynamic tumor microenvironment. This review focuses on the most recentadvances in 3D in vitro osteosarcoma models, highlighting the crucial role ofthe extracellular matrix and stromal cells in tumor progression, how theycontribute to drug resistance and disease prevalence, and the future pathwaystoward an effective and personalized model for drug screening and validation.